Optimalisasi Pemanfaatan Laboraturium Fisika Di SMAK Bhaktyarsa Maumere - Maria Reneldis Reginaldis Daelsi; Yuni Pantiwati (Jurnal Kebijakan dan Pengembangan Pendidikan, 2015)
Abstract: This study aims to determine: 1) How to optimize the use of laboratories at MaakereBhaktyarsa High School?; 2) What are the obstacles in the utilization of BhaktiyadMaumere SMAK Physics laboratory?; 3) What is the solution to overcome the problems encountered in the use of physics laboratories at the MaakereBhaktyarsa High School?. The approach used in this study is qualitative. Data collection methods used in this study were observation, interviews, and documentation. The data analysis method uses descriptive qualitative analysis which consists of four stages, namely data collection, data reduction, data display and conclusion drawing or verification. Data obtained from the results of observations, interviews, and triangulation of the principal, head of the laboratory and physics subject teachers at the MaakereBhaktyarsa High School. The results showed that 1) Optimization of the use of physics at Bhakt Audience High School was optimal, this was indicated by the completeness of facilities and infrastructure, improvement in the ability and understanding of teachers about laboratory use, changes in laboratory functions and managers; 2) Obstacles faced in the use of physics laboratories are the limited time available, the lack of awareness and enthusiasm of students in the use of laboratories and the activities that occur outside the planned schedule.(3) The solutions used in overcoming obstacles are (a) preparation of planning especially on the schedule of laboratory activities. (b) Before practicum students are always directed and motivated about the benefits of practicum activities or activities in the physics laboratory.Keywords: Optimization, Laboratory Utilization, Physics Abstrak: Penelitian ini bertujuan untuk mengetahui: 1) Bagaimana optimalisasi pemanfaatan laboratorium di SMAK BhaktyarsaMaumere?; 2) Apa Hambatan dalam pemanfaatan laboratorium  Fisika SMAK BhaktyarsaMaumere?; 3) Bagaimana solusi dalam mengatasi permasalahan yang dihadapi dalam pemanfaatan laboratorium fisika di SMAK BhaktyarsaMaumere?. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif. Metode pengumpulan data yang digunakan dalam penelitian ini adalah observasi, wawancara, dan dokumentasi. Adapun metode analisis data menggunakan analisis deskriptif kualitaitif yang terdiri dari empat tahapan yakni pengumpulan data, reduksi data, display data dan penarikan kesimpulan atau ferifikasi. Data diperoleh dari hasil observasi, wawancara dan triangulasi terhadap kepala sekolah, kepala laboratorium dan dan guru mata pelajaran fisika di SMAK BhaktyarsaMaumere. Hasil penelitian menunjukkan bahwa 1) Optimalisasi pemanfaatan fisika di SMAK Bhaktirsa sudah optimal, hal ini ditunjuk dengan kelengkapan sarana dan prasarana, peningkatan kemampuan dan pemahaman guru tentang pemanfaatan laboratorium, perubahan fungsi laboratorium dan pengelola. (2) Hambatan yang dihadapi dalam pemanfaatan laboratorium fisika yaitu keterbatasan waktu yang disediakan, minimnya kesadaran serta antusias siswa dalam pemanfaatan laboratorium dan adanya kegiatan yang terjadi diluar jadwal yang direncanakan. (3) Solusi yang digunakan dalam mengatasi hambatan yaitu (a) penyusunan perencanaan terutama pada jadwal kegiatan laboratorium. (b) Sebelum praktikum siswa selalu diarahkan dan diberi motivasi tentang manfaat kegiatan praktikum atau kegiatan dalam laboratorium fisika.Kata kunci: Optimalisasi, Pemanfaatan Laboratorium, Fisika